IMPLEMENTATION OF ESG PRINCIPLES IN UZBEKISTAN JOINTSTOCK COMPANIES AND THEIR IMPACT ON ISSUANCE ACTIVITY (World Bulletin of Management and Law, 2025)
The process of integrating ESG (Environmental, Social, Governance) principles into the activities of Uzbek joint-stock companies and the impact of this process on the issuance activity - issuance of shares and corporate bonds, capital structure and cost of capital is analyzed. In world practice, the existence of a predominantly positive or neutral relationship between ESG indicators and financial results and cost of capital has been proven by numerous meta-studies, and in recent years this trend has become relevant for emerging markets, including Uzbekistan. The study analyzes, on the one hand, the institutional framework for ESG, formed on the basis of state programs such as the “Uzbekistan-2030” strategy and the declaration of 2025 as the “Year of Environmental Protection and Green Economy”, and, on the other hand, the stages of state and corporate “green” and SDG bond issuance. In the empirical part, the relationship between ESG initiatives, social and environmental projects, improvement of the corporate governance system, and the bank’s net profit, profitability indicators, and bond issuance is analyzed on the basis of open data, using the example of one of the joint-stock companies in Uzbekistan, Kapitalbank JSC. The analysis shows that the systematic introduction of ESG principles affects the issuance activities of joint-stock companies in three ways: (1) a decrease in the cost of capital due to a decrease in financial and reputational risks; (2) improvement of supply and demand and pricing conditions for emission instruments (shares, “green” and SDG bonds); (3) expanding access to capital markets through increased communication with investors, international financial institutions, and rating agencies. In the final conclusions, the author puts forward practical recommendations for Uzbek joint-stock companies on integrating ESG principles into their issuance strategies.